Menuju Integritas Kampus: Mengintegrasikan Pendidikan Antikorupsi dengan Pendidikan Agama Islam - Ulum, Bachrul; Astutik, Leny Suryaning; Janattaka, Nugrananda; Zaini, Moh.; Riswadi, Riswadi; Amrullah, Zen (Program Pascasarjana UNU Surakarta, 2025)
The widespread corruption in Indonesia is a major obstacle to the country's economic and social progress. Instilling anti-corruption values in the next generation is a critical responsibility of higher education institutions. This study looks at how Islamic Religious Education classes in Indonesian universities have begun to incorporate lessons about against corruption. The faculty and students of Bhinneka PGRI University participated in a qualitative case study. Documentation, in-depth interviews, participant observation, and focus groups were used to obtain facts. The findings demonstrated that a number of strategies were employed to incorporate anti-corruption education into Islamic Religious Education courses. These included reviewing the curriculum and syllabus, creating interactive teaching materials and methods, and organising student activities to promote a culture that rejects corruption. Integrity, compassion, autonomy, discipline, responsibility, hard work, simplicity, courage, and fairness are nine anti-corruption principles that were found to be included in the course materials. Additionally, a number of successful learning strategies were implemented, including learning through projects, learning in context, learning in collaboration, learning through discovery, value clarification tools, and modelling good behaviour. Students are encouraged to cultivate their character and integrity through the incorporation of anti-corruption instruction within Islamic Religious instruction classes. This will equip them to take on leadership roles in the fight against corruption in the future. University syllabi should incorporate anti-corruption education, according to this report, and additional research into alternative learning modalities should be pursued to foster an anti-corruption culture on campus.